3, 3′-Diindolylmethane ameliorates renal fibrosis through the inhibition of renal fibroblast activation in vivo and in vitro. (15th October 2018) - Xia, Zun-En; Xi, Juan-Li; Shi, Lei
Abstract: 3, 3′-Diindolylmethane (DIM), a natural acid condensation extracted from cruciferous plants, exhibits anti-fibrotic effects in hepatic and cardiac fibrosis models. The effects of DIM on renal fibrosis, however, are unclear. This study aimed to explore the protective effects of DIM on renal fibrosis. Unilateral ureteral obstruction (UUO) and transforming growth factor (TGF)-β1-stimulated normal rat kidney (NRK)-49F fibroblast cell mouse models were established. The models were then treated with DIM for the assessment of its anti-fibrotic effects and mechanisms. Results of HE and Masson staining showed that DIM reduced kidney injury and production of interstitial collagens fibrosis. CTS also inhibited expression of fibronectin, collagen-1 but retain E-cadherin in the UUO model. Furthermore, DIM suppressed local fibroblast activation, as evidenced by the suppressed expression of the myofibroblast markers α-SMA and vimentin in vivo and in vitro . In addition, DIM significantly inhibited the TGF-β1-induced proliferation of NRK49F cells in a time- and dose-dependent manner. DIM decreased Smad2/3 phosphorylation but increased Smad7 expression. Results suggested that DIM inhibits TGF-β/Smad2/3 signaling to attenuate renal interstitial fibrosis via inhibiting local fibroblast activation. This mechanism is likely related to Smad7 induction.